2004
DOI: 10.1177/15257401040250030201
|View full text |Cite
|
Sign up to set email alerts
|

Three Aspects of Cultural Influence on Communication

Abstract: Children acquire communication skills within a socially and culturally influenced context. Communication professionals need to be aware of the ways cultural differences influence communication. This article describes the influence of cultural backgrounds on communication patterns along a continuum of behaviors. The purpose is to review relevant literature as an operating framework for professionals providing services to children and families from diverse cultural and linguistic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…These assumptions render clear distinctions in social-interactional responsibilities, power and risk management strategies that are aligned with the collectivist cultures (Hwa-Froelich & Vigil 2004). A closer examination of the lack of collaborative-consultation between the Malaysian SLPs and parents also revealed that many Malaysian SLPs have large work caseloads (Joginder Singh et al 2011) which reduces planning time for an effective collaborative-consultation approach that is transferable to the child's naturalistic environment.…”
Section: Early Language Intervention Services In Malaysiamentioning
confidence: 99%
See 3 more Smart Citations
“…These assumptions render clear distinctions in social-interactional responsibilities, power and risk management strategies that are aligned with the collectivist cultures (Hwa-Froelich & Vigil 2004). A closer examination of the lack of collaborative-consultation between the Malaysian SLPs and parents also revealed that many Malaysian SLPs have large work caseloads (Joginder Singh et al 2011) which reduces planning time for an effective collaborative-consultation approach that is transferable to the child's naturalistic environment.…”
Section: Early Language Intervention Services In Malaysiamentioning
confidence: 99%
“…This practice will not be embraced by parents if they don't perceive their child as equal partners in communication and if parents see the responsibility of leading the interaction as theirs rather than the child's. Following the child's lead may also be ineffective if parents believe that children hold little power when interacting with adults, and should therefore play a relatively passive role in social-interactions and produce only acceptable behaviours (Hwa-Froelich & Vigil 2004). Parallel to following the child's lead, success in collaborativeconsultation with parents require that both parents and SLP view each other as holding distinct responsibilities but equal power in the working relationship.…”
Section: General Beliefs On Language Teaching and Learning In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are some concerns about the results of the study. Cultural differences can raise different patterns of parent-child interaction (Hwa-Froelich & Vigil, 2004). For example, mothers from a Western culture tend to provide a more autonomous support for her child than mothers from an Asian culture.…”
Section: Introductionmentioning
confidence: 99%